The riverside Chaucer - Chaucer, Geoffrey,Benson, Larry Dean (Oxford Univ. Press, 1988)
Preface – Introductory note – Introduction – The Canterbury tales – The book of the dutchess – The house of fame – Anelida and Arcite – The parliament of fowls – Boece – Troilus and Criseyde – The legend of good women – The short poems – Poems not ascribed to Chaucer in the manuscripts – A treatise on the astrolabe [with ill.] – The romaunt of the rose – Appendix. Providing general information on the life, language and works that one needs for a first reading of Chaucer, this edition contains the materials for a more thorough understanding of Chaucer's works
9780192821096
Keywords: Chaucer; Geoffrey -1400 / Criticism and interpretation; Poetry in English; 1066-1400 - Texts